Fighting against COVID-19: With or without politics? - Kovanic, Martin; Steuer, Max (Social science & medicine (1982), 2023)
To respond to the COVID-19 pandemic, governments frequently resorted to declaring the state of emergency, fuelling contestations over the abuse of public powers and effectiveness of the measures to induce compliance. This article examines how the denial of the political nature of emergency governance known as depoliticisation undermines government credibility and may suit anti-democratic actors. We contribute to understanding the relationship between depoliticisation and democracy by showing how Slovak coalition parties during key parliamentary debates on the state of emergency during the COVID-19 pandemic insisted on depoliticising the pandemic while parliamentary opposition parties with anti-democratic leanings successfully opted for its repoliticisation. Repoliticising a key decision on managing the public health emergency granted credibility to illiberal political actors at the expense of the government, cautioning against depoliticisation strategies to be invoked by democrats in fragile democracies. Instead, accepting that such decisions are political may prevent the loss of credibility due to unsuccessful rhetorical practices of depoliticisation.
Keywords: Public Health; vláda; COVID-19; Pandemics; Humans; pandemie; politika; veřejné zdravotnictví; Politics; Government; lidé